A Comparative Analysis of Operational Efficiency and Product Quality in Steel Manufacturing: Traditional Processes vs. Smart Manufacturing Practices - Mohit Beniwal; Dr. Lalit Narayan (International Journal of Scientific Research in Science and Technology, 2024)
In this study, we delve into the transformative potential of smart manufacturing practices within the steel industry by conducting a comprehensive comparative analysis with traditional manufacturing processes. Through rigorous statistical analyses, including independent samples t-tests and effect size calculations, we scrutinize the differences in operational efficiency and product quality outcomes between these two manufacturing paradigms. Our findings offer empirical insights into the tangible benefits and potential drawbacks of adopting smart manufacturing technologies in steel production. By elucidating these differences, our research aims to inform strategic decision-making and investment priorities for industry stakeholders, policymakers, and academic researchers. This study contributes to the ongoing discourse on smart manufacturing adoption in the steel sector, providing empirical evidence to guide the industry towards enhanced competitiveness and sustainability.
Keywords: Smart manufacturing; Steel industry; Operational efficiency; Product quality; Comparative analysis; Traditional manufacturing; Statistical analysis; Effect size